Pembangunan program tropic untuk simulasi pembolehubah bumbung terhadap keselesaan dalaman di Malaysia - Hidayat, Muhammad Syarif (2004)
Building simulation program developed still refers to the research purpose. So, it is difficult for architects to evaluate their buildings, especially for naturally ventilated buildings. This thesis discusses the efforts to obtain a suitable building simulation program, which in turn can be used in conceptual stage. The main aim of this study is to develop building simulation program, which can be used in naturally ventilated buildings. In the first part of the thesis, the principles of passively controlled indoor temperature through building envelope are explained. The principles of heat gain calculation of each part of the building are also explained. The new computer programming, TROPIC, has been developed to calculate room air temperature. This program demonstrates sensitivity analysis, which use roof variables. The study indicates that insulation is the most sensitive parameter of the roof. The range of temperatures obtained in the living room is 1.7 0C. This parameter could achieve the lowest living room temperature as 29.3 0C. Parameters resulting lower indoor air temperature which run together in the program indicates a slightly lower air temperature than before, that is 29.2 0C. This temperature almost achieves the comfort range for Malaysian. This new program is expected to help architects and designers in evaluating their design in the preliminary design stage, so that the thermal indoor conditions would be better.